Cypella cruenta (Iridaceae), the blood-stained Cypella - Deble, Leonardo Paz (Balduinia, 2021)
Cypella cruenta (Iridaceae), the blood-stained Cypella. A new species of Cypella is described for the region of Camaquã river basin, in southeastern Rio Grande do Sul state, Brazil. The new species, named Cypella cruenta belongs to the section Cypella, being morphologically similar to the following species: Cypella Alonsoana, C. exilis and C. fucata. However, C. cruenta is easily recognized by its tepals with the concave portion and proximal half of the blade intensely painted in blood red, by the shape and size of the stamens and style with brief branches and with shorter crests, when compared with its similar taxa. Information on geographic distribution, ecology, conservation, uses and taxonomic relationships is provided. In addition, illustrations and a distinctive table among C. cruenta and its related species is presented. With the description of the new species, the genus Cypella now comprises 32 species, 17 of them belonging at section Cypella.